Pengaruh Minat Belajar terhadap Kemampuan Pemahaman Konsep Matematis Siswa SMP pada Materi Relasi dan Fungsi - Liana Sari (Didactical Mathematics, 2022)
This research is based on the low ability of students to understand mathematical concepts caused by two factors, namely internal factors and external factors. Interest in learning is an internal factor of students that is thought to affect the ability to understand students' mathematical concepts. This study aims to determine whether there is an influence of interest in learning on the ability to understand mathematical concepts of junior high school students in relation and function course. This research is a correlational quantitative research with survey method. The population in this study were grade VIII students of SMP Negeri 4 Karawang Barat in the 2021/2022 academic year. While the sampling was done using cluster random sampling technique and obtained class VIII C as many as 15 students. The instruments used are in the form of tests and non-tests, namely a test of the ability to understand mathematical concepts in relation and function course, and a questionnaire of interest in learning mathematics. Based on the results of data analysis obtained a significance value of 0.020 < 0.05, H0 is rejected and Ha is accepted which means that there is an influence of interest in learning on the ability to understand mathematical concepts of junior high school students in relation and function material with a coefficient of determination of 35.2% while the remaining 64.8 % is influenced by factors other than interest in learning mathematics.